INSTALLATION CONDITIONS OF SOLAR HOT WATER SUPPLY SYSTEMS - Mirzaliyev, B.B. (Educational Research in Universal Sciences, 2023)
In order to increase the efficiency of the water heater, the installation conditions are very important. This article describes the installation conditions in detail.